Competitive and value effects of bank privatization in developed countries - Otchere, Isaac (Journal of Banking & Finance, 2009)
A special issue of the Journal of Banking and Finance (2005) devoted to the performance of privatized banks in middle- and low-income countries shows mixed results. In this paper, we present evidence that shows that privatized banks in developed countries have experienced significant improvements in operating performance. The improvement in performance remains significant after controlling for persistence in bank performance. A comparison of the performance of privatized banks in developed and developing countries suggests that privatization has encouraged excessive risk taking among privatized banks in developing countries, with the consequence that those banks carry large non-performing assets than their counterparts in the developed countries. We also observe that consistent with the competitive effects hypothesis, investors view privatization announcements as foreshadowing bad news for rival banks.